The Concept of Syariat Teaching in Samawi Religion in The Works of The Story of Civilization By Will Durant: Samawi Religion in The Works of The Story of Civilization by Will Durant - Tumadi, Nurul Hidayah; Ritonga, Husein; Hasan, Hadri; Kirin, Arwansyah (Journal of Techno-Social, 2021)
Islam is major religion in the three categories of another samawi religions in the world, containing syariat teachings such as hijab (veil), polygamy, maintaining a halal and good diet, limiting mixing between men and women and so on. Various problems that arise among Muslims about the teachings of the Syariat, some are compliant with the Syariat and some are violate it to the point of cornering Islam in the eyes of other religions. While infact other samawi religions also have syariat teachings that are not much different from the Islamic teachings that we follow. Therefore, this study aims to identify the concept of samawi religious teachings according to Will Durant through his work The Story of Civilization so that the similarities and differences between the religions can be indentified. Another goal in this study is that every application of the law that concerning the application of religious law is actually not only Islam, but in reality in other samawi religions, the Shari'a has been set which is not much different. The methodology of this study is qualitative through the method of literature and content analysis design of the book The Story of Civilazation. This study found that there are similarities in the concepts of the teachings of the samawi religion (Jewish, Christian/Christian and Islamic). Although some concepts the teachings of the syariat are not explained in detail by Will Durant on some religions, as he is more focused on history, politics and the concept of faith. Another goal is that every application of the law that leads to the application of Islamic law is actually not only Islam but in essence other divine religions have also been stipulated by the Shari'a which is not much different. This research proves this. Therefore, this study can give us understanding that if the concept of sharia teachings in this heavenly religion is carried out correctly, then there will be no difference between human beings but will be a form of religious tolerance, especially to Islam.